PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION (GI) DI SD - Desmawati, Desmawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study aims to improve the learning process so that IPS can improve student learning outcomes in the classroom five subject areas of social science at SDN 28 East Rawang Padang. The results of the analysis of research data can be inferred from the results of the lesson plan in the first cycle 1 meeting, the average value is 70.55 cognitive, affective and psychomotor 66.11 68.26. Cycle I 74.07 2 meeting, cognitive, affective and psychomotor 70.74 71.33. Cycle II meeting 1 the average value was 77.96 cognitive, affective and psychomotor 75.8 76.8. In the second cycle 82.59 2 meeting, cognitive, affective and psychomotor 78.26 78.56.   Kata Kunci : hasil belajar, pembelajaran IPS, tipe group investigation (GI)